On the Outside: Prisoner Reentry and Reintegration - Harding, David J. (University of Chicago Press, 2019)
Intro -- Contents -- Acknowledgments -- Introduction -- Chapter 1. Trajectories -- Chapter 2. Transitions -- Chapter 3. A Place to Call Home? -- Chapter 4. Families and Reintegration -- Chapter 5. Navigating Neighborhoods -- Chapter 6. Finding and Maintaining Employment -- Conclusion -- Appendix: Data and Methodology -- Notes -- References -- Index